Gaba islamiyat lazmi book 2 - Yousaf Zai, Zia ul Haq (Gaba educational books Karachi, 2011)
This book is offering a structured introduction to essential Islamic concepts and values. Through age-appropriate language and engaging activities, it encourages young learners to develop a strong understanding of their faith. Perfect for fostering spiritual growth and moral development in early education.